Termination of pregnancy. Issue 7 (July 2017) - Pykett, Rowena; Smith, Stephen C.
Abstract: With at least one in three women in the UK having a termination of pregnancy (TOP) by the age of 45, provision of termination services forms a key part in the role of any obstetrician and gynaecologist. Despite this, there is still stigma attached and formal teaching is frequently missing from the curriculum of trainees. This review aims to explain and discuss the basics of providing termination of pregnancy services, address some of the less frequently encountered difficulties and consider some of the ethical and religious implications that can influence practice.